(untitled) (Experimental biology, 2024)
Bipolar disorder is a mental disease expressed in repeating maniac, depressive and euthymic phases of human behaviour. Different studies have found that changes in the expression or mutations of specific genes are involved in the progress of this disease. These genes encode the proteins participating in the transmission of nerve impulses (such as mediators, ion channels, etc.), endocrine regulation of mood and other processes. As we know, the expression of many human protein-coding genes is regulated on the post-transcriptional level by miRNAs (microRNAs) binding with mRNAs of the genes and blocking their translation. So, recent studies have also shown that some miRNAs can regulate the expression of genes connected with human bipolar disorder. But which of these miRNAs are specific for this mental disease? What is their role in these processes? What are the applications of this data for the diagnosis, prevention and therapy of human bipolar disorder? We will try to answer these questions in our review article.